2019
DOI: 10.1007/s12525-019-00341-2
|View full text |Cite
|
Sign up to set email alerts
|

Platform-based collaboration in digital ecosystems

Abstract: Organizations operating in a network require strong information technology support to successfully collaborate. In a business service network, the links between partners must enable quick connect and disconnect relationships, in order to harness market opportunities. Scholars claim that information technology platforms are necessary to enhance this quick connect capability and to transform business networks into digital ecosystems. However, the state of the art in inter-organizational collaboration relies on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…In this review, we identified 20 design requirements for EP design. Based on these 20 requirements four design categories were derived that provide an overview of essential success factors for EP: (1) easing the entry, (2) identifying mutual problems and needs, (3) supporting value co-creation and (4) facilitating service innovation [15]. These categories address a number of activities and challenges already established in platform literature.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…In this review, we identified 20 design requirements for EP design. Based on these 20 requirements four design categories were derived that provide an overview of essential success factors for EP: (1) easing the entry, (2) identifying mutual problems and needs, (3) supporting value co-creation and (4) facilitating service innovation [15]. These categories address a number of activities and challenges already established in platform literature.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consequently, EPs are supposed to establish processual and institutional structures that improve the exchange of services [5]. Activities and mechanisms to improve co-creation include: involving external actors and communities to improve the density of co-creation on EPs [5,23], coordinating of interaction, and providing freedom to (collaboratively) introduce new and improved offerings among heterogenous actors [2]. While the support of value co-creation in the service ecosystems that utilize EPs is essential [20], attracting and maintaining a critical mass of actors, relies on the ability to introduce new, as well as to improve the existing, offerings, and the overall service experience [8].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations